PERNIKAHAN WANITA HAMIL DI LUAR NIKAH TINJAUAN MENURUT EMPAT MADZHAB - Rionaldi (LPPM-IAI BATAM, 2023)
In modern times the phenomenon of marriage of pregnant women outside of marriage is quite frequent. In general, the marriage takes place between a pregnant woman out of wedlock and a married person, sometimes also with someone else who has never touched her. Pregnancy without first marriage is certainly a gross sin and violates the principles and rules of Islamic law. In this context, scholars disagree on whether to marry a pregnant woman without going through marriage. The results of this study showed that Imama Abu Hanifah and Al-Syafi argued that pregnant women out of wedlock do not have iddah, so it is okay to marry. The permission to marry a woman who is pregnant out of wedlock is based on the hadith of Prophet Muhammad Saw,